Sistem Informasi Inventarisasi Barang Pada Dinas Perhubungan Kota Jambi - Hamzah, Erik; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2022)
The Jambi City Transportation Service is an agency / agency engaged in transportation for the Jambi City Government. The problem that occurs at the Jambi City Transportation Department is that the recording of inventory items such as damaged and repaired goods is still manual so that often errors occur in recording and loss of supervision of these assets. The purpose of this study is to design an inventory information system at the Jambi City Transportation Agency. The method used in system design is the prototyping method. While the system modeling tools used by the author are Use Case Diagrams, Activity Diagrams, Class Diagrams. This inventory information system prototype is expected to make it easier for the Jambi City Transportation Agency to carry out inventory and control goods as well as facilitate the preparation of reports. So as to be able to produce the information needed quickly, precisely and accurately.